The incidence and relative risk of pulmonary toxicity in patients treated with anti-PD1/PD-L1 therapy for solid tumors: a meta-analysis of current studies. (June 2017) - Ciccarese, Chiara; Iacovelli, Roberto; Bria, Emilio; Modena, Alessandra; Massari, Francesco; Brunelli, Matteo; Fantinel, Emanuela; Bimbatti, Davide; Zamboni, Giulia A; Artibani, Walter; Tortora, Giampaolo
Aim: Monoclonal antibodies (mAbs) directed against PD-1/PD-L1 have recently entered the therapeutic algorithm of several solid tumors. Among treatment-related adverse events pulmonary toxicity (PT) is of particular interest. We assess the incidence and relative risk (RR) of PT in patients treated with anti-PD1/PD-L1 mAbs.Results: 11 articles were selected. The incidence of any- and high-grade PT was low (2.9 and 1.0%, respectively). Compared with standard therapies, anti-PD-1 mAbs do not significantly increase the risk of both any-grade (RR: 2.65; p = 0.06) and high-grade PT (RR: 1.40; p = 0.25). Of note, the RR: of developing any-grade (RR: 3.13; p < 0.0001) and high-grade (RR: 2.42; p = 0.03) PT significantly increased when excluding the Checkmate-025 trial, with everolimus as control therapy. No differences were identified between the type of mAbs, the tumor type and treatment duration for both any-grade and high-grade PT.